Modified lumbar foraminoplasty using a power-aided reciprocating burr for percutaneous transforaminal endoscopic lumbar discectomy: A technical note and clinical report - Wang, Yingbo; Wu, Jian; Wang, Tengyu; Liu, Yaoyao; Jiang, Mei; Wang, Zhong; Chao, Rui; Liu, Peng; Pu, Jungang; Fan, Weili (Frontiers in Surgery, 2023)
Background: One of the main difficulties in a transforaminal endoscopic lumbar discectomy (TELD), and simultaneously the most critical step, is performing an effective and safe foraminoplasty, which is especially difficult for beginners. To make it safer and faster for beginners to perform, we have used a specially designed power-aided reciprocating burr for TELD and reported the technical details. Methods: From Jan. 2019 to Nov. 2022, 432 patients with single-level, symptomatic L4/5 or L5/S1 disc herniation were treated with TELD using a novel power-aided reciprocating burr. The surgical procedure is described in detail. Magnetic resonance imaging (MRI) was performed the following day and 3 months after the operation. The learning curves of surgeons with different seniority levels are displayed. The Visual Analogue Scale (VAS) score and the Oswestry Disability Index (ODI) were used to measure low back pain, leg pain, and lumbar function. All patients were followed up for at least 1 year. Results: All patients underwent endoscopic surgery successfully. Among the 432 patients, radicular outer membrane damage was observed in 6 cases, and 1 case had herniation of the nerve tract. Except for this patient with aggravation of postoperative numbness, the postoperative neurological symptoms of all patients were significantly improved. The mean VAS scores for low back pain and leg pain and ODI scores were significantly decreased 6 w post-operatively and were maintained until 12 months post-operatively compared to preoperative scores (P < 0.05). All three doctors involved in the study had substantial experience in traditional open spinal surgery. The more operations all three surgeons completed, the more time spent on intervertebral foraminoplasty decreased (P < 0.05). Among them, doctors without experience in TELD surgery became proficient in this technique after accumulating experience in 13 cases. There was no significant difference in foraminoplasty time among these three surgeons during the same growing period (P >0.05). Conclusions: Current clinical data demonstrated the safety and efficacy of modified TELD using a power-aided reciprocating burr for treating lumbar disc herniation (LDH) and showed that this technique significantly reduces the learning curve for beginners when performing foraminoplasty.